Effects of Alternative Seating on the Academic Engagement of Children With Autism - Tunstall, Hillary R. (East Carolina University, 2010)
Students with sensory integration deficits may display a hyper or hyposensitivity to sensory information and lack the ability to modulate that input in socially appropriate ways. Therapy balls as a sensory integration intervention has shown positive results for use with fourth grade students with attention deficit hyperactivity disorder and preschool children with autism. Therapy balls were used to improve classroom behavior and improve student engagement to relevant materials and persons. Therapy balls are large, inflatable balls, often used for exercise. This form of intervention is thought to afford students with autism who may have deficits in their ability to modulate sensory input the chance to do this in an appropriate way. Students can bounce or roll on the ball which aids in sensory modulation without being disruptive to instruction. The current study replicated the Schilling and Schwartz (2004) study with high school students with autism in a self-contained class. The study examined the effects of therapy balls as seating on in-seat behavior and on-task behavior. Momentary time sampling was used to ascertain the percentage of time that each participant is in-seat/on-ball and on-task/academically engaged. Participants were recruited from a local high school self-contained class for students with autism and include one male and one female student. Single-case design methodologies were used to examine the results. For each participant, data was collected in four phases, two using typical seating and two using the proposed intervention. Participant's data indicate that the therapy ball intervention was initially helpful in improving on-task behavior but that improvement was not replicated after a withdrawal of the intervention. For both participants, in-seat behavior remained appropriate and was therefore, not the focus of this intervention.
Keywords: Psychology, Behavioral; Autistic children--Behavior modification; Behavior modification; Sensory integration dysfunction in children; Autistic children--Education